Sosialisasi Stop Pernikahan Dini Sebagai Upaya Pencegahan Penurunan Angka Stunting Di Desa Air Seruk, Sijuk, Belitung - Pratiwi, Najwa (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Stunting is a condition of growth failure in children caused by malnutrition in the long term. Toddlers suffering from stunting are often identified by their body shape which is much shorter or stunted when compared to the height of children of their age. Based on basic health research from the Ministry of Health in 2018, it shows that 1 in 3 children in Indonesia have stunting. This condition is certainly a big problem for all of us, not only duties for the government or medical personnel but also the wider community, especially housewives, to pay more attention to the nutritional intake of their children. Therefore, our goal in socializing the dangers of early marriage is as an effort to prevent stunting in the Air Seruk area. The implementation method for this activity is in the form of outreach regarding stopping early marriage targeting young people in the village, for example: Youth Posyandu, and also PIK-R with a total of 30 participants. The outreach activities received support from local midwives and also the Air Seruk health center. Conclusion: Early marriage has an impact on inadequate parenting patterns as a result of the mother's limited knowledge and the potential for nutritional struggles between the mother and fetus during pregnancy. Therefore, early marriage is considered to be one of the factors causing stunting.